REGIONAL ORGANISATIONS AND CRISIS MANAGEMENT: ASEAN AND GCC’S APPROACHES TO ROHINGYA CRISIS - Siti Darwinda Mohamed Pero; Norafidah Ismail, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2018)
The Article 52 of the UN Charter has stated that local disputes should be settled regionally before referral to the United Nations and that resolution via the Security Council remains an option if regional efforts fail (Nguyen 2006: 463). This implies that one of the key roles of a regional organisation is in crisis management, and only then, peace and stability in that particular region could be maintained and guaranteed. This paper seeks to examine the effectiveness of Association of Southeast Asian Nations (ASEAN) and Gulf Cooperation Countries (GCC) in crisis management. This paper examines the policy behaviours of ASEAN and GCC, as well as individual member state’s reactions towards Rohingya crisis. It also seeks to analyse the extent to which the motivations behind these reactions have been profoundly framing the institutional and individual policies on the grim fate of Rohingya people